(3GdUYhHGJ GdJi JhGLg eeGQSI GdfTGW GdeSQMi GdeOQSi ai eOjfI HZOGO h SHd eYGdLJgG (B/ s - (3YHO GdGdg eMeO LGSes; (3UHGM YWjI ShjHL (B: s ((3HZOGO (B: s (3YHO GdGdg eMeO LGSe (B: s, 2013)
(3gOa GdHMK GdMGdi GdcTa Yf GdUYhHGJ GdJi JhGLg eeGQSI GdfTGW GdeSQMi ai HZOGO(B. (3GbJQGM SHd eYGdLI Jdc GdUYhHGJ(B. (3dJMbjb GgOGa GdHMK(B: (3bGe GdHGMK HUjGZI abQGJ GdGSJHjGf ai VhA GdOQGSI GdGSJWdGYjI GdJi GLQGgG Ydi eTQai GdfTGW GdeOQSi(B. (3h jYO Gf Je YQVgG Ydi GdGSGJPI GdNHQGA ef Phi GdGNJUGU h MSH GdGUhd GdeJHYI Je JWHjb GdGSJHjGf HTcdg GdeZdb Ydi eLJeY GdHMK GdPi Jchf ef eTQai GdfTGW GdeSQMi ai eOjQjJi JQHjI GdQUGaI(B/(31(B: (3h GdcQN(B/(32 h GdHGdZ YOOge (B(30) (3KdGKjf eTQaG h eTQaI(B: (3eNJUjf HGdGTQGa Ydi GdfTGW GdeSQMi GdeOQSi(B: (3h dGXgGQ fJGFL GdHMK GYJeO GdHGMK eYGOdI ajTQ dMSGH GdhSW GdeQLM h GdhRf GdeFhi h bO JVef GdGSJHjGf (B(25) (3NeSI h YTQjf abQIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI HZOGO (B- ((3hRGQI GdJYdje GdYGdi h GdHMK GdYdei(B) - (3cdjI Gdafhf GdLejdI (B- (3bSe GdJQHjI GdafjIs